Differential mitochondrial genome in patients with Rheumatoid Arthritis - Kumar Sagar Jaiswal; Shweta Khanna; Arup Ghosh; Prasanta Padhan; Sunil Kumar Raghav; Bhawna Gupta (Taylor & Francis Group, 2021)
Background Mitochondria play an important role in cell survival, function and lineage differentiation. Changes in mitochondrial DNA (mtDNA) may control mitochondrial functions and thus may impart an alternative cellular state thereby leading to a disease condition in the body. Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease wherein immune cells become self-reactive causing joint inflammation, swelling and pain in patients. The changes in mtDNA may alter cellular functions thereby directing the immune cells towards an inflammatory phenotype in RA. Therefore, it becomes pertinent to identify changes in mtDNA sequence in immune cells of RA patients to understand the pathogenesis and progression of RA. Methods mtDNA from peripheral blood mono-nuclear cells (PBMCs) of 23 RA patients and 17 healthy controls (HCs) were sequenced using next-generation sequencing (NGS). Further, single nucleotide polymorphisms (SNPs) and other variable changes in mtDNA hypervariable and coding regions, amino acid changes with a putative impact on disease, levels of heteroplasmy, copy number variations and haplogroup analysis in RA patients and HCs were analysed and compared to identify any association of mtDNA changes and RA disease. Results A total of 382 single nucleotide mtDNA variants were observed, 91 (23.82%) were present in hypervariable region and 291 (76.18%) in coding region of patients and HC. The variant 513 GCA > ACA, with G present in HVR-III, known to control the mitochondrial translation function, was significantly present in RA patients. The CYTB gene had larger number of SNPs in HC samples while RNR2 was more variable in RA patients. A non-synonymous heteroplasmy in ND1 gene was found at a single nucleotide position 3533 in an increased number of RA patients as compared to the controls. A significant increase in mtDNA duplication and a higher frequency of the haplogroup U was also characteristic of RA. Also, the presence of SNPs in mitochondrial tRNA genes at two positions 12308 A > G and 15924 A > G were found to be pathogenic. Conclusion We herein observed an altered mtDNA sequence in immune cells of RA patients and thus a possible role of mitochondrial genome in the development of RA. The observed nucleotide changes in mtDNA control region, RNR2 gene, increased heteroplasmy and mtDNA duplication in RA patients may alter sites for transcription factor binding thereby influencing mtDNA gene expression, as well as copy numbers thereby affecting the mitochondrial proteins and their functions. These changes in mtDNA could be one of the probable reasons among many leading to the progression of RA.